Perbandingan Tindakan (Practices) Berjalan Kaki Sebelum Dan Di Masa Pandemi Covid-19 Berdasarkan Gender (Studi Kasus: Mahasiswa Universitas Komputer Indonesia): Comparison Of Walking Practices Before And During The Covid-19 Pandemic By Gender (Case Of Study : Indonesian Computer University Students) - Mohamad Donie Aulia; Romeiza Syafiharti; Pipih Paliah (Media Ilmiah Teknik Sipil, 2023)
The purpose of this study was to determine differences in the act of walking before and during the Covid-19 pandemic based on gender. Walking is the highest level in the sustainable transport pyramid. The research method used is descriptive qualitative comparative. Data collection was done through a questionnaire, with the respondents being Unikom students. The results of this study indicate that walking for transportation (X1), exercising (X2), relaxing (X3), walking on weekdays (X4), walking on weekends (X5), and walking duration/duration (X6) are dominant. gender of women than men in conditions before and during the Covid-19 pandemic. Comparison of X1, X2, X3 in women and men shows that the frequency of walking has increased for exercise during the COVID-19 pandemic. Comparisons X4, X5 in women, showed that the behavior of walking was 6% greater in frequency on weekdays than weekends, while in men there was no difference or the same frequency of walking on weekdays and weekends. The duration of walking for women is 8% longer than for men